Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the quadratic equation [tex]\(x^2 - 6x + 4 = 0\)[/tex] by completing the square, follow these steps:
1. Start with the given equation:
[tex]\[ x^2 - 6x + 4 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 - 6x = -4 \][/tex]
3. Complete the square on the left side:
- Take half of the coefficient of [tex]\(x\)[/tex] (which is [tex]\(-6\)[/tex]), divide by 2, and square it:
[tex]\[ \left(\frac{-6}{2}\right)^2 = 9 \][/tex]
- Add and subtract this value to/from the left side:
[tex]\[ x^2 - 6x + 9 - 9 = -4 \][/tex]
- Rearrange the equation:
[tex]\[ (x - 3)^2 - 9 = -4 \][/tex]
4. Move the constant term [tex]\(-9\)[/tex] to the right side to isolate the square term:
[tex]\[ (x - 3)^2 = 5 \][/tex]
5. Take the square root of both sides:
[tex]\[ x - 3 = \pm \sqrt{5} \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = 3 + \sqrt{5} \quad \text{or} \quad x = 3 - \sqrt{5} \][/tex]
So, the solutions for the quadratic equation [tex]\(x^2 - 6x + 4 = 0\)[/tex] are:
[tex]\[ x = 3 + \sqrt{5} \quad \text{and} \quad x = 3 - \sqrt{5} \][/tex]
1. Start with the given equation:
[tex]\[ x^2 - 6x + 4 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 - 6x = -4 \][/tex]
3. Complete the square on the left side:
- Take half of the coefficient of [tex]\(x\)[/tex] (which is [tex]\(-6\)[/tex]), divide by 2, and square it:
[tex]\[ \left(\frac{-6}{2}\right)^2 = 9 \][/tex]
- Add and subtract this value to/from the left side:
[tex]\[ x^2 - 6x + 9 - 9 = -4 \][/tex]
- Rearrange the equation:
[tex]\[ (x - 3)^2 - 9 = -4 \][/tex]
4. Move the constant term [tex]\(-9\)[/tex] to the right side to isolate the square term:
[tex]\[ (x - 3)^2 = 5 \][/tex]
5. Take the square root of both sides:
[tex]\[ x - 3 = \pm \sqrt{5} \][/tex]
6. Solve for [tex]\(x\)[/tex]:
[tex]\[ x = 3 + \sqrt{5} \quad \text{or} \quad x = 3 - \sqrt{5} \][/tex]
So, the solutions for the quadratic equation [tex]\(x^2 - 6x + 4 = 0\)[/tex] are:
[tex]\[ x = 3 + \sqrt{5} \quad \text{and} \quad x = 3 - \sqrt{5} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.